Study The Potential Application Of Smart Fluid Material And Force Tracking Control Of Magnetorheological Damper - Harun, Mohd Hanif; W Abdullah, Wan M Zailimi; Jamaluddin, Hishamuddin; Ab Rahman, Roslan; Hudha, Khisbullah; Harun, Mohamad Hafiz (Trans Tech Publications, 2014)
The aim of this paper is to study the potential application of magnetorhelogical (MR)fluid as a smart material used in semi-active damper of a vehicle suspension system.An MR damper was designed and fabricated and tested in the laboratory using damper test machine.The non-linear behaviour of the MR damper is modelled using third order polynomial model based on experimental data.Force tracking control is carried out in order to track the ability of the MR damper to produce force as close as possible with the desired force. Continuous state control is chosen for the inner loop controller of the MR damper.The performance of the proposed controller as a force-tracking controller is compared with the desired force produced by vehicle system.The results of the study shows that the proposed controller is able to track the desired force successfully.